Assessing the extent of compliance of multinational corporations with the United Nations guiding principles on business and human rights in Ghana - Maziwisa, Michelle (University of Pretoria, 2023)
Mini Dissertation (MPhil (Human Rights and Democratisation in Africa))--University of Pretoria, 2023.